Managing Language Development in Film Production: Leveraging the Metaverse and VR for Enhanced English Proficiency and Workforce Efficiency - Piayura, Orathai; Boonmas, Thidarat; Wongphongkham, Niyom; Sae-joo, Phongthanat; Narongchai, Wanichcha; Ahbab, Md Ahbabur Rahman (Journal of Ecohumanism, 2024)
This study investigates the potential of Virtual Reality as an instructional tool for improving English language skills in the Thai film industry. The research gauges the effectiveness of the "EngLab for Film" VR-based learning application, evaluating its impact on student engagement, motivation, and independent learning. As a result of the global shift to digital education due to COVID-19, this study investigates how immersive technologies like VR can support language development and workforce efficiency. Insights gathered and analysed from feedback provided by 100 participants revealing that VR can significantly boosts language proficiency, learner motivation, and workforce efficiency. Moreover, further improvements in technical and content design are necessary for optimal outcomes.